Clustered star formation at early evolutionary stages: physical and chemical analysis of the young star-forming regions ISOSS J22478+6357 and ISOSS J23053+5953 - Gieser, Caroline; Beuther, Henrik; Semenov, Dmitry; Suri, Sümeyye; Soler, Juan D.; Linz, Hendrik; Syed, Jonas; Henning, Thomas; Feng, S.; Möller, T.; Palau, A.; Winters, J. M.; et al. (Astronomy and astrophysics, 2022)
Context. The process of high-mass star formation during the earliest evolutionary stages and the change over time of the physical and chemical properties of individual fragmented cores are still not fully understood.Aims. We aim to characterize the physical and chemical properties of fragmented cores during the earliest evolutionary stages in the very young star-forming regions ISOSS J22478+6357 and ISOSS J23053+5953.Methods. NOrthern Extended Millimeter Array 1.3 mm data are used in combination with archival mid- and far-infrared Spitzer and Herschel telescope observations to construct and fit the spectral energy distributions of individual fragmented cores. The radial density profiles are inferred from the 1.3 mm continuum visibility profiles, and the radial temperature profiles are estimated from H2CO rotation temperature maps. Molecular column densities are derived with the line fitting tool XCLASS. The physical and chemical properties are combined by applying the physical-chemical model MUlti Stage ChemicaL codE in order to constrain the chemical timescales of a few line-rich cores. The morphology and spatial correlations of the molecular emission are analyzed using the histogram of oriented gradients (HOG) method.Results. The mid-infrared data show that both regions contain a cluster of young stellar objects. Bipolar molecular outflows are observed in the CO 2−1 transition toward the strong millimeter (mm) cores, indicating protostellar activity. We find strong molecular emission of SO, SiO, H2CO, and CH3OH in locations that are not associated with the mm cores. These shocked knots can be associated either with the bipolar outflows or, in the case of ISOSS J23053+5953, with a colliding flow that creates a large shocked region between the mm cores. The mean chemical timescale of the cores is lower (~20 000 yr) compared to that of the sources of the more evolved CORE sample (~60 000 yr). With the HOG method, we find that the spatial emission of species that trace the extended emission and of shock-tracing molecules are well correlated within transitions of these groups.Conclusions. Clustered star formation is observed toward both regions. Comparing the mean results of the density and temperature power-law index with the results of the original CORE sample of more evolved regions, it appears that neither change significantly from the earliest evolutionary stages to the hot molecular core stage. However, we find that the 1.3 mm flux, kinetic temperature, H2 column density, and core mass of the cores increase in time, which can be traced both in the M/L ratio and the chemical timescale, τchem.